All‐Solid‐State, Washable, Wearable Supercapacitors Fabricated by using a Fibrous Graphite Network and Self‐Adhering Architecture. Issue 8 (26th June 2014) - Park, Soomin; Yoo, Young Geun; Nam, Inho; Bae, Seongjun; Yi, Jongheop
Abstract An all‐solid‐state, completely foldable, washable supercapacitor system fabricated by using a taping method is reported. A constructed graphitic fiber network derived from conventional graphite felt was readily assembled into a full‐cell by utilizing self‐adhering architecture. The as‐prepared system exhibits good mechanical properties under various folding motifs, and the supercapacitor is washable without capacitance fading by virtue of the robust electrical connectivity of the fibrous graphite network and intimate contact between the polymeric gel electrolyte and the electrodes. A simple surface oxidation of the electrode greatly enhances the capacitance of the system (≈313 μF cm−2) by reducing the charge separation distance at the electrolyte/electrode interface. The results suggest that this supercapacitor system is a promising candidate for practically available and wearable energy storage systems with high cost effectiveness and scalability.